2014
DOI: 10.1371/journal.pone.0091473
|View full text |Cite
|
Sign up to set email alerts
|

E2 Proteins of High Risk Human Papillomaviruses Down-Modulate STING and IFN-κ Transcription in Keratinocytes

Abstract: In the early stages of human papillomavirus (HPV) infection, the viral proteins elicit specific immune responses that can participate to regression of ano-genital lesions. HPV E6 protein for instance can reduce type I interferon (IFN) including IFN-κ that is involved in immune evasion and HPV persistence. To evaluate the role of E2 protein in innate immunity in HPV16-associated cervical lesions, genome-wide expression profiling of human primary keratinocytes (HPK) transduced by HPV16 E2 was investigated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 53 publications
2
77
0
2
Order By: Relevance
“…This is the first report of a possible involvement of STING in HPV immunity. Furthermore, knockdown of STING moderately reduced IFN-expression in primary human KC, and both proteins were reduced in HPV-positive cervical tissue and CIN1 (60). IFN-downregulation in HPV-positive precursor lesions and cervical cancer has been observed before (64,65).…”
Section: Kc As Mediators Of Innate Immunitymentioning
confidence: 91%
See 2 more Smart Citations
“…This is the first report of a possible involvement of STING in HPV immunity. Furthermore, knockdown of STING moderately reduced IFN-expression in primary human KC, and both proteins were reduced in HPV-positive cervical tissue and CIN1 (60). IFN-downregulation in HPV-positive precursor lesions and cervical cancer has been observed before (64,65).…”
Section: Kc As Mediators Of Innate Immunitymentioning
confidence: 91%
“…High-risk HPV oncoproteins are effective suppressors of ISG expression (58)(59)(60). The E6 and E7 oncoproteins from HPV16 and -31 inhibit both STAT1 (61), an essential mediator of IFN signaling, and PKR (40), which is increased by IFN-␣/␤/␥ to induce translation inhibition.…”
Section: Kc As Mediators Of Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative analysis of ISG transcription in cells with complete 16, 18 and 31 genomes suggests that this is via the inhibition of the constitutive transcription of IFN-κ [21]. The HPV 16 and 18 E2 protein suppresses many genes associated with innate immunity and, in particular, the expression of STING and IFN-κ [22], the first report of a possible involvement of STING in HPV innate sensing. In contrast, hrE5 enhances IFN-β and IRF1 expression [23].…”
Section: Hrhpvs Downregulate Interferon Responsesmentioning
confidence: 99%
“…Studies have also shown that the oncoproteins encoded by high-risk HPV types such as E2, E6, and E7 target immune responsive genes, downregulate their expression facilitating immune eva-sion, persistent viral infection, and HPV persistence. E2 protein, via its transactivation amino-terminal domain, has shown to suppress IFN-κ and STING gene expression [113] .…”
Section: The Immune System Epigenetics and Cervical Cancermentioning
confidence: 99%